IS THERE A LINK BETWEEN SUNLIGHT EXPOSURE AND 25-HYDROXYVITAMIN D DEFICIENCY IN CHRONIC KIDNEY DISEASE PATIENTS? - Angela Yee-Moon Wang; Iris Hiu-Shuen Chan; Christopher Wai-Kei LAM (The Korean Society of Nephrology, 2012)
There is an increasing global recognition of nutritional vitamin D deficiency in patients with chronic kidney disease (CKD). Yet, there is not much data in the Chinese population. We performed this prospective cross-sectional survey, with an aim to determine the prevalence of vitamin D deficiency (defined as serum 25-hydroxyvitamin D [25(OH)D] level <30ng/mL) in a cohort of Chinese stage 3-5 CKD patients and factors associated with its deficiency. Two-hundred and fifty (157 men and 93 women) stage 3-5 CKD patients (mean age: 57±12 years) were invited to have blood taking for 25(OH)D levels and other biochemical parameters and were asked to record the average number of hours of outdoor sunlight exposure per day during weekday and weekend in the week before blood taking. The mean glomerular filtration rate (GFR) estimated by the MDRD equation was 25±13 ml/min per 1.73m2, with 84, 91 and 75 patients having stage 3, 4 and 5 CKD. Two hundred and twenty-six patients (90%) were confirmed to be 25(OH)D deficient with 97% of the women having 25(OH)D deficiency as compared to 87% of men. In the univariate analysis, both weekday and weekend outdoor sunlight exposure showed significant positive association with serum 25(OH)D levels. In the multiple linear regression analysis, younger age (P<0.001), fewer weekday sun exposure hours (P<0.001) and female gender (P=0.001) were found to be the most significant factors associated with lower serum 25(OH)D levels. In conclusion, our study confirmed an extremely high prevalence of vitamin D deficiency and an important association between outdoor sunlight exposure and 25(OH)D deficiency in Chinese stage 3-5 CKD patients. Further study is needed to determine whether increasing daily outdoor sunlight exposure may represent a cost-free treatment for correcting nutritional 25(OH)D deficiency in the CKD population.